2005
DOI: 10.1097/01.mlg.0000176544.72657.a6
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Innervation of the Anterior Maxilla: A Cadaver Study with Relevance to Canine Fossa Puncture of the Maxillary Sinus

Abstract: There is significant variation in the pattern of ASAN and MSAN within the anterior face of the maxilla. By using the newly described landmarks when performing a canine fossa puncture, there is reduced risk of damage to these nerves and provides a reliable point to enter the maxillary sinus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 11 publications
1
52
0
4
Order By: Relevance
“…The infraorbital nerve supplies the skin and midface mucosa. When it emerges on the face by the infraorbital foramen, the infraorbital nerve is divided into three alveolar proximal branches (anterior, middle, and posterior superior alveolar nerves) and four distal branches (inferior palpebral, external nasal, internal nasal and superior labial) [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…The infraorbital nerve supplies the skin and midface mucosa. When it emerges on the face by the infraorbital foramen, the infraorbital nerve is divided into three alveolar proximal branches (anterior, middle, and posterior superior alveolar nerves) and four distal branches (inferior palpebral, external nasal, internal nasal and superior labial) [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…There is some discussion as to the need for CFT in the treatment of rhinosinusitis. 2,4 The majority of findings are that CFT offers the potential for complete clearance of mucosal disease in the maxillary sinus. Interestingly, Lee et al 4 noted no significant difference in the outcome for patients with chronic rhinosinusitis and nasal polyposis treated with CFT versus MMA without CFT; however, the patients in this group did not have allergic fungal sinusitis, and it is recognized that incomplete clearing of fungal mucin results in a rapid recurrence of the disease.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, an updated anatomical study has described new landmarks, namely a trephination at the intersection of the midpupillary line and the horizontal line through the floor of the nasal vestibule. 2 Cadaveric studies have shown this to be the optimum position for avoiding damage to the plexuses of the anterior superior alveolar nerve (ASAN) and middle superior alveolar nerve (MSAN), and the potential sequelae of cheek swelling, dental numbness, facial numbness, tingling, and pain.…”
Section: Introductionmentioning
confidence: 99%
“…(6) The complications of the CFP are cheek swelling, facial pain, facial numbness, cheek pain, dental numbness, gingival complications and facial tingling which are the result of injury to branches of the infraorbital nerve as illustrated by Robinson et al (7) To decrease the risk of complications, the site of puncture in canine fossa is an intersection between the mid-pupillary line and a line through the floor of the nasal vestibule as advocated as landmark by Wormald PJ et al In our study, we advocate the same site of puncture as described by Wormald P J et al (8) Only one patient complains of facial numbness, immediate post-operative period which resolve at third-month interval.…”
Section: Discussionmentioning
confidence: 99%